Pilot study using intraoperative fluorescence angiography during arteriovenous hemodialysis access surgery - Regus, Susanne; Klingler, Felix; Lang, Werner; Meyer, Alexander; Almási-Sperling, Veronika; May, Matthias; Wüst, Wolfgang; Rother, Ulrich (Journal of Vascular Access, 2019)
Introduction: In this pilot study, we used indocyanine green fluorescence angiography during hemodialysis access surgery. The aim was to evaluate its relevance as a diagnostic tool to visualize changes in hand microperfusion. Patients and methods: In this prospective single-center study, 47 adult patients (33 male, 14 female) with renal disease (24 preemptive, 23 endstage) were enrolled. Surgical creation of an arteriovenous fistula was performed (22 forearm, 25 upper arm). Microperfusion of the ipsilateral hand and fingers was evaluated intraoperatively using indocyanine green fluorescence angiography. We compared the cumulated microperfusion parameters ingress (In) and ingress rate (InR) before and after opening of the anastomosis. To compare the dimension of microcirculatory decline, we calculated the ratios of the parameters (RatioIn and RatioInR) after to those before anastomosis opening. Results: The cumulated microperfusion parameters In and InR showed a significant decrease after completion of anastomosis and declamping. This effect has been seen in all patients for the hand and for each finger consecutively. During follow-up (mean 4.6, range 3-11 months), 5 patients (10.6%) complained about hemodialysis access-induced distal ischemia. The ratio of intraoperative microperfusion in those five hemodialysis access-induced ischemia patients was significantly lower compared to asymptomatic patients (RatioIn 0.23 vs 0.58, p = 0.001, and RatioInR 0.25 vs 0.62, p = 0.003). Conclusion: Intraoperative fluorescence angiography could visualize the deterioration of ipsilateral hand microperfusion after surgical creation of an arteriovenous fistula. It seems to be a promising tool to detect patients at risk for hemodialysis access-induced distal ischemia early in the peri- or even intraoperative stage.
CRIS-Team WoS Importer:2019-03-06